INTERNASIONALISASI BAHASA INDONESIA DI ASEAN: SUATU UPAYA DIPLOMATIK INDONESIA - Gilang Nur Alam; Emil Mahyudin; RMT Nurhasan Affandi; Windy Dermawan; Fuad Azmi (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
This paper aims to analyze Indonesia's diplomatic efforts in promoting Indonesian as the official language of ASEAN. To achieve this goal, the author describes Indonesia's leadership in ASEAN which has been accepted as a natural leader. The author also describes the possibility and position of Indonesian as the official language in ASEAN. The method used is a qualitative method while the findings of this study are that Indonesian has the potential to become an international language, for this purpose it is necessary for all levels of society to realize this dream, starting from strengthening in the country such as revitalization and diplomatic efforts that are not only carried out by diplomats, but with the various innovations and technologies currently available, every society needs to be an agent of language internationalization whose hopes will raise the image of the Indonesian nation in the international world which will ultimately affect the Indonesian nation as a whole.